Estudo comparativo entre métodos de avaliação da vulnerabilidade natural de aquífero, aplicado na porção oriental da bacia sedimentar do Parnaíba no município de Tianguá - Ceará - Sousa, Rafael Rolim de (2016)
When talk about groundwater it must to attempt to the aquifers vulnerability, cause where occur transport, storage and it register, more or less contaminant protection to different types of sources. Thus, it is important hydrogeological characterization of aquifers, to know the limits and areas which are more susceptible to contamination by natural or anthropogenic factors. Considering these aspects, this study compared the DRASTIC, AVI, GOD and GODS natural vulnerability evaluation models of the aquifer contamination, into the Serra Grande Aquifer, corresponding to Tianguá country. Beyond the comparison between the vulnerability models, the purpose of this study is to relate the chosen model with the nitrate analysis and the use and land occupation. The result of the comparison between models showed that the best model applied in studied area was DRASTIC. Through this comparison was observed that the results differences are related to work resolution and scale, where the first is directly linked to the amount of parameters analyzed and, second, the size area to be studied. Thus, the application of DRASTIC model for small areas and, like his case study, with only one type of lithology, demonstrated a level of detail greater than the other models. The indexes found for DRASTIC model ranged from 90 to 176 and they were divided in the classes: insignificant, very low, low, moderate and high. The results showed to 96.3% for nitrate that analyzes are below the maximum allowed value. This value should not be disregarded because these concentrations are associated with intensive use of nitrogenous fertilizers, moreover, 77.8% of analyzed wells are in deforested areas to agricultural practices. The integration of this information has generated a map of the relationship between the DRASTIC model and use and land occupation which, is intended to assist managers and society to establish efficient of land use and occupation, thus ensuring greater protection for aquifers. The result of this integration has shown that the best regions with availability for the occupation are those classified with low vulnerability, because they present some distance along the riverbanks and are associated with gently undulating reliefs. Areas with very low to negligible vulnerability are associated with undulating and mountainous reliefs, making it difficult to occupation of the territory. The high and moderate vulnerability zones should be those with lower occupancy rates to be associated with planed geomorphological features, however have a high rate of occupation, be it by urbanization or arable areas.